Negative electrode material, preparation method and lithium ion battery
By using a combination of transition metal carbodiimide and conductive polymer in the negative electrode material of lithium-ion battery, a layered structure and a pore structure are formed, which solves the problem of low cyclic stability of the negative electrode material in the prior art, and achieves high energy density and excellent cycling performance.
Patent Information
- Application Number
- CN202411583635.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-11
AI Technical Summary
The existing lithium-ion battery anode materials have large interface resistance and low cycle stability during the cycle process, resulting in capacity attenuation and cannot meet the needs of high energy density and cycling performance.
The negative electrode material including transition metal carbodiimide as the active substance and conductive polymer as the shell layer is used. The transition metal carbodiimide is coated with conductive polymer to form a layered structure and a pore structure, improve the ion storage density, and promote electrochemical reactions through the electron transport path of the conductive polymer.
It improves the capacity and circulation performance of the battery, enhances the structural stability and lithium storage performance of the material, and reduces the risk of interface resistance and particle powdering.
Smart Images

Figure BDA0005123770130000071 
Figure BDA0005123770130000081 
Figure BDA0005123770130000082
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of battery materials, and specifically relates to a negative electrode material and a preparation method, and a lithium-ion battery. Background Art
[0002] At present, the rapid development of mobile technologies, including portable consumer electronics and electric vehicles, has strongly stimulated the demand for high energy density and cycle performance of lithium-ion batteries. In order to build high-performance lithium-ion batteries, the development of high-capacity negative electrode materials has attracted widespread attention, such as metal coordination compounds, which have great development potential in the field of energy storage.
[0003] However, metal coordination compounds with higher energy density often have larger interfacial resistance during cycling and lower cycle stability, which can easily lead to capacity decay problems and cause unsatisfactory battery performance.
[0004] How to provide a negative electrode material with high energy density and stable cycle performance is a problem that needs to be solved at present. Summary of the invention
[0005] The present application provides a negative electrode material and a preparation method, and a lithium-ion battery, aiming to solve the problem that existing negative electrode materials cannot meet the requirements of lithium-ion batteries for high energy density and cycle performance.
[0006] In order to solve the above problems, the first embodiment of the present application provides a negative electrode material, including an active substance and a shell layer coated on the surface of the active substance; the active substance includes transition metal carbodiimide, and the shell layer includes a conductive polymer;
[0007] Wherein, the chemical formula of the transition metal carbodiimide is M[N(CN)2] x ; M is a transition metal, x=1~4.
[0008] In some embodiments, the mass ratio of the active substance to the shell layer is (1-5): (0.1-10).
[0009] In some embodiments, the molecular weight of the conductive polymer is 200-2000.
[0010] In some embodiments, the average thickness of the shell layer is 50-1000 nm.
[0011] In some embodiments, the conductivity of the conductive polymer is 10 -3 ~10 6 S / cm.
[0012] In some embodiments, the transition metal includes at least one of iron, cobalt, nickel, manganese, and zinc.
[0013] In some embodiments, the conductive polymer includes at least one of polypyrrole, polythiophene, and polyaniline.
[0014] The second embodiment of the present application provides a method for preparing a negative electrode material, which is used to prepare the negative electrode material in any of the above embodiments, comprising the following steps:
[0015] Providing a carbodiimide salt and a transition metal source, mixing them for a first reaction, and obtaining a transition metal carbodiimide;
[0016] A conductive polymer monomer is provided, mixed with the transition metal carbodiimide in water, an oxidant is added, and a second reaction is performed to obtain the negative electrode material.
[0017] In some embodiments, the molar ratio of the carbodiimide salt to the transition metal source is (0.1-5):(0.1-5);.
[0018] In some embodiments, the molar ratio of the transition metal carbodiimide, the monomer of the conductive polymer, and the oxidant is 1:(0.5-5):(0.1-5).
[0019] In some embodiments, the carbodiimide salt includes at least one of Na[N(CN)2], K[N(CN)2], and Li[N(CN)2].
[0020] In some embodiments, the transition metal source includes at least one of zinc chloride, iron chloride, nickel chloride, manganese chloride, and cobalt chloride.
[0021] In some embodiments, the monomer of the conductive polymer includes at least one of pyrrole, thiophene, and aniline.
[0022] In some embodiments, the oxidizing agent includes at least one of ammonium persulfate, hydrogen peroxide, ferric chloride, and ferric perchlorate.
[0023] In some embodiments, before the step of performing the second reaction, the method further comprises:
[0024] Adding dispersant;
[0025] Wherein, the molar ratio of the transition metal carbodiimide to the dispersant is 1:(0.1-5);
[0026] In some embodiments, the dispersant includes at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, dodecylbenzene sulfonic acid, and toluene sulfonic acid.
[0027] A third embodiment of the present application provides a lithium-ion battery, comprising a negative electrode sheet, wherein the negative electrode sheet comprises the negative electrode material in any of the above embodiments or the negative electrode material prepared by the preparation method in any of the above embodiments.
[0028] The present application provides a negative electrode material, comprising an active substance and a shell layer coated on the surface of the active substance; the active substance comprises a transition metal carbodiimide, and the shell layer comprises a conductive polymer; wherein the chemical formula of the transition metal carbodiimide is M[N(CN)2] x ; M is a transition metal, x=1 to 4. The negative electrode material provided in the present application uses an inorganic nitrogen-containing transition metal material as an active material, comprising a complex [N(CN)2] - Anions have a layered structure and therefore have a higher specific surface area and pore structure, which makes it easier for ions in the electrolyte to embed and de-embed into the layered material. This embedding / de-embedding reaction can achieve a higher ion storage density, thereby increasing the capacity of the battery; on the other hand, the conductive polymer as a protective shell coating the transition metal carbodiimide is conducive to the rapid transmission of electrons on the surface of the negative electrode material, promoting the electrochemical reaction kinetics of the material, resulting in superior structural stability and lithium storage performance during the charge and discharge cycle. . DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the embodiments in the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0030] In the description of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or can communicate with each other; it can be directly connected, or indirectly connected through an intermediate medium, or indirectly connected through a pipe or pipeline, and it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to the specific circumstances. In the description of the present application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. In addition, the terms "first" and "second" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" can explicitly or implicitly include one or more features.
[0031] In order to solve the above problems, the first embodiment of the present application provides a negative electrode material, including an active material and a shell layer coated on the surface of the active material; the active material includes transition metal carbodiimide, and the shell layer includes a conductive polymer;
[0032] The chemical formula of transition metal carbodiimide is M[N(CN)2] x ; M is a transition metal, x=1~4.
[0033] M[N(CN)2] x Contains complex [N(CN)2] - Anions have a layered structure and therefore have a higher specific surface area and pore structure, which makes it easier for ions in the electrolyte to embed and de-embed into the layered material. This embedding / de-embedding reaction can achieve a higher ion storage density, thereby increasing the capacity of the battery. On the other hand, a single M[N(CN)2] x During the cycle, the interface resistance is large, and the particles are prone to pulverization and breakage, which eventually leads to capacity decay. Conductive polymers are used as coatings for M[N(CN)2] x protective shell, which can form M[N(CN)2] x The electron transmission pathway between particles reduces the ion diffusion resistance and reduces M[N(CN)2] x The risk of particle pulverization enhances the stability of the material structure and further improves the lithium storage performance of the negative electrode material.
[0034] In some embodiments, the mass ratio of the active substance to the shell layer is (1-5):(0.1-10).
[0035] When the mass ratio of the active material to the shell layer satisfies the above value, it can ensure that the active material in the negative electrode material has an ideal effective capacity, and at the same time ensure that the active material has an ideal stability.
[0036] In some embodiments, the molecular weight of the conductive polymer is 200-2000.
[0037] The molecular weight in this application refers to the weight average molecular weight of the polymer molecules. It is understood that the molecular weight of the conductive polymer can be any value of 200, 500, 800, 1000, 1300, 1600, 1800, 2000 or a range between any two values. When the molecular weight of the conductive polymer meets the above range, it can ensure that the conductive polymer body has good conductivity and mechanical strength.
[0038] In some embodiments, the average thickness of the shell layer is 50-1000 nm.
[0039] It is understood that the average thickness of the shell layer (unit: nm) can be any value of 50, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000 or a range between any two values.x A thicker conductive polymer can provide better mechanical stability and protection, but too thick a conductive polymer shell may lead to the formation of M[N(CN)2] x The transport paths of ions and electrons are too long, which reduces M[N(CN)2] x The effective utilization rate of the active material affects the electrical performance of the battery. When the average thickness of the shell layer meets the above value range, the negative electrode material as a whole can have good mechanical stability and electrical performance.
[0040] In some embodiments, the conductivity of the conductive polymer is 10 -3 ~10 6 S / cm.
[0041] It is understood that the conductivity of the conductive polymer (unit: S / cm) can be 10 -3 , 10 -2 , 10 -1 , 1, 10, 10 2 , 10 3 , 10 4 , 10 5 , 10 6 Any value or a range between any two values in . Conductive polymers need to have good electrical conductivity so that the negative electrode material has an ideal discharge rate and output power. However, if the electrical conductivity of the conductive polymer is too high, electrons may be transferred too quickly between the active material and the electrode, thereby reducing the internal resistance of the battery, causing the battery to discharge too quickly and shortening the battery life. Therefore, when the electrical conductivity of the conductive polymer meets the above range, it can provide good electronic conduction performance and balance the power output and energy density of the battery.
[0042] In some embodiments, the transition metal includes at least one of iron, cobalt, nickel, manganese and zinc, and zinc is more preferably used. The preparation method of the β-polycrystalline of Zn[N(CN)2]2 is simple, and lithium ion storage can be performed through conversion reaction and alloy reaction. In addition, the bond between zinc and carbodiimide group is relatively strong, which can provide better material stability.
[0043] In some embodiments, the conductive polymer includes at least one of polypyrrole, polythiophene, and polyaniline.
[0044] The second embodiment of the present application provides a method for preparing a negative electrode material, which is used to prepare the negative electrode material in any of the above embodiments, comprising the following steps:
[0045] Providing a carbodiimide salt and a transition metal source, mixing them for a first reaction, and obtaining a transition metal carbodiimide;
[0046] A conductive polymer monomer is provided, mixed with transition metal carbodiimide in water, an oxidant is added, and a second reaction is performed to obtain a negative electrode material.
[0047] The preparation method of the negative electrode material provided in the present application adopts a liquid phase oxidative polymerization method. Under the action of an oxidant and a dispersant, the monomer undergoes oxidative polymerization in an aqueous solution, and is tightly combined with a transition metal carbodiimide active substance through forces such as van der Waals forces and hydrogen bonds, and finally a new negative electrode material with a coating layer structure is constructed. This method only needs to control conventional parameters such as the proportion of raw materials, reaction time and temperature, and has no strict requirements on other experimental conditions. The method is simple, inexpensive, environmentally friendly, and has extremely high repeatability and feasibility.
[0048] In some embodiments, the molar ratio of the carbodiimide salt to the transition metal source is (0.1-5):(0.1-5).
[0049] When the molar ratio of the carbodiimide salt to the transition metal source satisfies the above value range, it can be ensured that the two can fully carry out coordination reaction to generate transition metal carbodiimide.
[0050] In some embodiments, the molar ratio of the transition metal carbodiimide, the conductive polymer monomer, and the oxidant is 1:(0.5-5):(0.1-5).
[0051] When the molar ratio of the transition metal carbodiimide, the conductive polymer monomer and the oxidant satisfies the above-mentioned range of values, the conductive polymer monomer can be fully oxidatively polymerized, while ensuring that the active material formed by the transition metal carbodiimide and the shell formed by the conductive polymer have an ideal mass ratio, thereby ensuring that the active material in the negative electrode material has an ideal effective capacity and that the active material has an ideal stability.
[0052] In some embodiments, the carbodiimide salt includes at least one of Na[N(CN)2], K[N(CN)2], Li[N(CN)2].
[0053] In some embodiments, the transition metal source includes at least one of zinc chloride, iron chloride, nickel chloride, manganese chloride, and cobalt chloride.
[0054] In some embodiments, the oxidizing agent includes at least one of ammonium persulfate, hydrogen peroxide, ferric chloride, and ferric perchlorate.
[0055] In some embodiments, before the step of performing the second reaction, the method further comprises:
[0056] Add dispersant.
[0057] By adding a dispersant, the surface tension of the transition metal carbodiimide and the conductive polymer monomers in the solution can be reduced, which promotes their dispersion and stability in the solution, helps to form a uniform reaction system, and improves the reaction efficiency and product quality.
[0058] In some embodiments, the molar ratio of transition metal carbodiimide to dispersant is 1:(0.1-5).
[0059] In some specific embodiments, the negative electrode material can be prepared by the following steps:
[0060] S1. Mix a carbodiimide salt and a transition metal source in a certain molar ratio and dissolve them in deionized water to form a white precipitate;
[0061] S2, centrifuging the precipitate several times, washing with water and ethanol, and drying at high temperature to obtain transition metal carbodiimide;
[0062] S3, weighing appropriate amounts of transition metal carbodiimide, conductive polymer monomer, and oxidant, ultrasonically dispersing them in deionized water, adding the dispersant solution dropwise, and stirring continuously for a certain period of time;
[0063] S4. After the stirring is completed, the mixture is centrifuged several times, washed with water and ethanol, and dried at high temperature to finally obtain the negative electrode material.
[0064] In some embodiments, the dispersant includes at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, dodecylbenzene sulfonic acid, and toluene sulfonic acid. Since the sulfonic acid group is hydrophilic, the above substances containing sulfonic acid groups can interact with water molecules to form a hydration layer, so that the transition metal carbodiimide and the monomer of the conductive polymer are dispersed in the solution to form a uniform reaction system, thereby improving the reaction efficiency and the quality of the product.
[0065] A third embodiment of the present application provides a lithium-ion battery, comprising a negative electrode sheet, wherein the negative electrode sheet comprises the negative electrode material in any of the above embodiments or the negative electrode material prepared by the preparation method in any of the above embodiments.
[0066] The following is a description of the negative electrode material and preparation method and the lithium ion battery provided by the present application in combination with specific embodiments:
[0067] Example 1
[0068] Example 1 provides a negative electrode material, which is prepared by the following steps:
[0069] S1. Mix Na[N(CN)2] and ZnCl2 in a molar ratio of 2:1 and dissolve them in 80 mL of deionized water to form a white precipitate.
[0070] S2. The precipitate was centrifuged several times, washed with water and ethanol, and dried at 60°C for 12 h to obtain Zn[N(CN)2]2 material.
[0071] S3. Weigh appropriate amounts of Zn[N(CN)2]2, pyrrole monomer, and sodium dodecylbenzene sulfonate, disperse them in 100 mL of deionized water by ultrasonic, and add ammonium persulfate solution dropwise. The solution concentration is 0.06 M. The molar ratio of Zn[N(CN)2]2 material, pyrrole monomer, sodium dodecylbenzene sulfonate, and ammonium persulfate is 1:1:1:1.5, and the mixed solution is stirred for 10 hours.
[0072] S4. After stirring, the mixture was centrifuged several times, washed with water and ethanol, and dried at 60°C for 12 h to finally obtain PPy / Zn[N(CN)2]2 material.
[0073] Embodiments 2 to 6
[0074] The preparation method of the negative electrode material provided in Example 2 is consistent with that in Example 1, and the only difference is the adjustment of the reactants and the addition ratio.
[0075] Comparative Example 1
[0076] Comparative Example 11 provides a negative electrode material, which is prepared by the following steps:
[0077] S1. Mix Na[N(CN)2] and ZnCl2 in a molar ratio of 2:1 and dissolve them in 80 mL of deionized water to form a white precipitate.
[0078] S2. The precipitate was centrifuged several times, washed with water and ethanol, and dried at 60°C for 12 h to obtain Zn[N(CN)2]2 material.
[0079] Comparative Examples 2 to 4
[0080] The preparation method of the negative electrode material provided in Comparative Example 2 is consistent with that in Example 1, the only difference being the adjustment of the reactants and the addition ratio.
[0081] The substances and related parameters in Example 1 and Comparative Example 1 are shown in Table 1.
[0082] Table 1
[0083]
[0084]
[0085] The materials prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were respectively used as negative electrode active materials, and negative electrode slurry was prepared according to the following ratio: negative electrode active material: conductive carbon black: binder CMC: SBR (90:5:2.5:2.5, mass ratio). Metal lithium sheet was used as the counter electrode, 1M LiPF6+EC / DEC (the volume ratio of LiPF6 to EC / DEC was 1 / 3) was used as the electrolyte, and polypropylene film was used as the separator. The battery was assembled according to the conventional method.
[0086] The button cell was placed on the CT2001A blue battery test system for charge and discharge performance test. The charge and discharge rate was 0.5C and the voltage range was 0.01-3.00V.
[0087] The test results are shown in Table 2.
[0088] Table 2
[0089]
[0090]
[0091] According to Table 1 and Table 2, it can be seen that the negative electrode material provided by the present application is a shell layer formed by a conductive polymer that coats the active substance, and has good performance in both charging capacity and cycle performance. According to Comparative Example 1, it can be seen that compared with the negative electrode material directly formed by the active substance without a shell layer, the negative electrode material provided by the present application has a significant improvement in charging capacity and cycle performance. According to Comparative Example 2, it can be seen that during the preparation process, excessive oxidant may cause the conductive polymer to produce by-products in the polymerization reaction, which has an adverse effect on the conductivity of the shell. According to Comparative Example 3 and Comparative Example 3, it can be seen that too much conductive polymer monomer addition leads to too thick a shell layer, or too little conductive polymer monomer addition leads to too thin a shell layer, which will lead to a decrease in the cycle performance of the battery.
[0092] The above is a detailed introduction to a negative electrode material and a preparation method, and a lithium-ion battery provided in the embodiments of the present application. Specific examples are used in the present application to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solution and its core idea of the present application. Ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A negative electrode material, characterized in that: It comprises an active substance and a shell layer coated on the surface of the active substance; the active substance comprises transition metal carbodiimide, and the shell layer comprises a conductive polymer; Wherein, the chemical formula of the transition metal carbodiimide is M[N(CN)2] x ; M is a transition metal, x=1~4.
2. A negative electrode material according to claim 1, characterized in that: The mass ratio of the active substance to the shell layer is (1-5): (0.1-10); and / or, The molecular weight of the conductive polymer is 200-2000.
3. A negative electrode material according to claim 1, characterized in that: The average thickness of the shell layer is 50 to 1000 nm.
4. A negative electrode material according to claim 1, characterized in that: The conductivity of the conductive polymer is 10 -3 ~10 6 S / cm.
5. A negative electrode material according to claim 1, characterized in that: The transition metal comprises at least one of iron, cobalt, nickel, manganese and zinc; and / or, The conductive polymer includes at least one of polypyrrole, polythiophene and polyaniline.
6. A method for preparing a negative electrode material according to any one of claims 1 to 5, characterized in that: The steps include: Providing a carbodiimide salt and a transition metal source, mixing them for a first reaction, and obtaining a transition metal carbodiimide; A conductive polymer monomer is provided, mixed with the transition metal carbodiimide in water, an oxidant is added, and a second reaction is performed to obtain the negative electrode material.
7. The method for preparing a negative electrode material according to claim 6, characterized in that: The molar ratio of the carbodiimide salt to the transition metal source is (0.1-5):(0.1-5); and / or, The molar ratio of the transition metal carbodiimide, the monomer of the conductive polymer and the oxidant is 1:(0.5-5):(0.1-5).
8. The method for preparing a negative electrode material according to claim 6, characterized in that: The carbodiimide salt comprises at least one of Na[N(CN)2], K[N(CN)2] and Li[N(CN)2]; and / or, The transition metal source comprises at least one of zinc chloride, iron chloride, nickel chloride, manganese chloride and cobalt chloride; and / or, The monomer of the conductive polymer includes at least one of pyrrole, thiophene and aniline; and / or, The oxidant includes at least one of ammonium persulfate, hydrogen peroxide, ferric chloride and ferric perchlorate.
9. The method for preparing a negative electrode material according to claim 6, characterized in that: Before the second reaction step, the method further comprises: Adding dispersant; Wherein, the molar ratio of the transition metal carbodiimide to the dispersant is 1:(0.1-5); and / or, The dispersant includes at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, dodecylbenzene sulfonic acid and toluene sulfonic acid.
10. A lithium ion battery, comprising a negative electrode sheet, characterized in that: The negative electrode sheet comprises the negative electrode material as described in any one of claims 1 to 5 or comprises the negative electrode material prepared by the preparation method as described in claims 6 to 9.
Citation Information
Patent Citations
Polypyrrole coated copper oxide nano-material for lithium ion battery, and preparation method thereof
CN108063220A
Polypyrrole doped shell composite positive electrode material and preparation method thereof
CN111509203A
Pre-lithiated silica material, preparation method and application thereof, and lithium ion battery
CN117476904A
Preparation method and application of soft carbon coated carbodiimide iron composite material
CN117976874A
Metal dicyandiamide negative electrode material
CN118016881A